Beyond rigidity: obtain localisability with noisy ranging measurement. (29th July 2011) - Wang, Xiaoping; Yang, Zheng; Luo, Jun; Shen, Changxiang
Location awareness is crucial for wireless networks, attracting many research efforts in recent years. One of the fundamental problems of localisation is to determine whether or not a network is uniquely localisable. To address this problem, existing approaches often adopt the rigidity theory, which assumes accurate inter-node distance measurements. Considering the measurement errors, we introduce the concept of strong localisability and propose an algorithm, called LAS, to identify and locate a kind of strongly localisable networks. Besides, we further conduct extensive simulations to show the performance of LAS design.